The Chasm of Structural Discrimination: Women on the Frontline Against COVID-19 - Naseva, Gala (Identities: Journal for Politics, Gender and Culture, 2020)
The swift and unceasing spread of COVID-19 has created a new wave of complications that have revealed dozens of issues dishevelled in the gendered and obsolete state management and in the low levels of social development, primarily focusing on the Balkans. With the onset of the pandemic, women with specific diseases belong to the most critical group, given the fact that infection with COVID-19 itself increases the risk of subsequent development of numerous health complications. This text briefly highlights the negative effects of the pandemic on women from several perspectives, trying to fleetingly show its severe impact on a global level and the necessity to improve a system that is barely surviving on already unsteady grounds. Author(s): Gala Naseva Title (English): The Chasm of Structural Discrimination: Women on the Frontline Against COVID-19 Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 2-3 (Winter 2020) Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 90-93 Page Count: 4 Citation (English): Gala Naseva, “ The Chasm of Structural Discrimination: Women on the Frontline Against COVID-19,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 2-3 (Winter 2020): 90-93. Author Biography Gala Naseva, Researcher Gala Naseva (1992, Skopje) is a legal researcher and interdisciplinary artist. She is currently the main editor of the multilingual Association of Young journalists from the Balkans Platform. Naseva completed her LLM in Intellectual Property Law at CEIPI, Strasbourg University and is now finishing the MA program in Gender Studies at ISSHS, North Macedonia. She was a visiting student at Justus Liebig University, Germany (Applied Theatre Studies and Musicology departments). Naseva worked as a legal consultant for the Helsinki Committee of Human Rights, USAID, The National Democratic Institute and OSCE (ODIHR). She has been engaged in the process of harmonizing various domestic legal acts with EU legislation.